"How Prevalent is Compensatory Consumption among 18-35 year olds: Specifically Investigating, Identification, Classification, Manifestation and Experiential elements" - Neve, Rachel Elizabeth (2006)
Of note, this article principally based upon Woodruffe-Burtons (1998) exploratory study, investigating the role of clothes as compensatory consumption in mens lives. In contrast to this paper however, this article purports to go beyond that of an experimental study, providing a holistic analysis of the compensatory consumption phenomena, introducing the preliminary findings of Woodruffe-Burtons (1998) study and current literature, but moreover building upon it with the participants enlisted throughout this study. This investigation therefore, not only explores the nature of compensatory consumption in men, but also probes its manifestation similarly throughout women. In addition to the exploration of fashion however, and perhaps its quite obvious links to compensatory consumption behaviour elicited, other arguably less tangible themes demonstrated amongst candidates are also investigated. Themes such as, body image and confidence deficits, specific life occasions, emotional attachments, retailer and brand relationships and boredom all of which have fuelled compensatory consumption, which form the crux of the further analysis undertaken in this article.